Hierarchical nitrogen-doped carbon nanotube-carbon nanofiber-based networks for electrochemical capacitors - Mofokeng, Thapelo Prince (My University, 2021)
In this thesis, various electrode materials were fabricated and investigated as electrode materials for supercapacitor applications. This research investigated the electrochemical properties of nitrogen-doped carbon nanotubes supported on electrospun carbon nanofiber networks (N-CNT@CF) hybrid material in symmetric and asymmetric capacitors. In addition, the storage kinetics of various energy storage mechanisms were thoroughly investigated. Field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), powder X-ray diffraction (P-XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and Brunauer-Emmett-Teller (BET) analysis were used to determine morphology, crystallinity, defects, elemental composition and the structural porosity of all the materials synthesized. In addition, electrochemical techniques such as cyclic voltammetry (CV), galvanostatic charge-discharge (GCD),electrochemical impedance spectroscopy (EIS)and cycle stability tests were performed for all materials in aqueous electrolytes using both the three (3) and two (2) electrode configurations. Firstly, a hierarchical nanostructure of nitrogen-doped CNTs supported on electrospun CNF networks (N-CNT@CF) was synthesized using two simple techniques: electrospinning and chemical vapour deposition (CVD). The N-CNT@CF hybrid structure revealed that uniform N-CNTs were directly grown on the surface of carbon nanofiber networks, resulting in the creation of a hierarchical nanostructure with a high surface area and high porosity. The interactions between N-CNTs and CF networks were discovered to improve the electrical conductivity and electrochemical stability of the material. As a result of the unique hierarchical structure and physicochemical properties, the as-synthesised N-CNT@CF composite material demonstrated exceptional electrochemical performance with a reversible specific capacitance, outstanding rate capability and long cycling stability. The symmetric device (N-CNT@CF//N-CNT@CF) on the other hand, showed a specific energy density of 5.5 Wh kg-1 with a power density of 254 W kg-1. The real-world practical application of N-CNT@CF electrode material was shown by powering an LED bulb. Secondly, a hybrid supercapacitor device was assembled with N-CNT@CF as the negative electrode and AT-Ni/MOFDC as the positive electrode. The hybrid device designated N-CNT@CF//AT-Ni/MOFDC shows a specific capacity of 10 mAh g-1at 0.5 A g-1. In comparison to the symmetric device (N-CNT@CF//N-CNT@CF), the N-CNT@CF//AT-Ni/MOFDC hybrid capacitor exhibits a higher energy density of about 8 Wh kg-1 with a power density of 400 W kg-1, as well as excellent cycling performance (94 % capacity retention after 2,000 cycles). An asymmetric supercapacitor (ASC) device was also assembled with N-CNT@CF as the negative electrode and Na0.44MnO2 as the positive electrode. The ASC device designated as N-CNT@CF//Na0.44MnO2 shows a high gravimetric and volumetric capacitance of 47 F g-1, 86 Fcm-3, respectively. Furthermore, a high energy density of 21 Wh kg-1and a power density of 450 W kg-1were obtained at 0.5 Ag-1. Finally, an asymmetric supercapacitor device operated in a “water-in-salt” electrolyte was developed, using Na0.44MnO2nanowiresand N-rGO as positive and negative electrodes, respectively. The N-rGO//Na0.44MnO2ASC device was operated in a wide potential between 0 and 3 V in AWIS aqueous electrolyte and exhibits a maximum specific capacitance of 61 F g −1. The energy density of 75.8 Wh kg−1 at a power density of 1125W kg −1 was obtained and remains 31 Wh kg −1 at a power density of 7500 W kg −1. Thus, the results obtained from this study show that the unique 3D hierarchical N-CNT@CF networks is a promising electrode material and can be used as an anode material for asymmetric supercapacitors
A thesis submitted to the School of Chemistry, Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021